Evaluation of the Prevalence and Risk Factors for Undernutrition in Hospitalized Dogs - Molina, Jenifer; Hervera, Marta; Manzanilla, Edgar Garcia; Torrente, Carlos; Villaverde, Cecilia (Frontiers in Veterinary Science, 2018)
Hospitalized dogs are predisposed to undernutrition, which can potentially affect outcome. This study evaluated the prevalence of undernutrition in hospitalized dogs (measured as loss of body condition score, BCS and body weight, BW) and studied the risk factors that affect nutritional status, and outcome (discharge or death). Data was collected prospectively during 9 months from 500 hospitalized dogs with a hospitalization length longer than 24 hours in a veterinary teaching hospital in Spain. The BCS and BW changes were modeled using multiple linear regression and outcome was modeled using logistic regression. The risk factors studied were energy intake, hospitalization length, initial BW and BCS, age, sex, severity of clinical signs, department of admission, fasting or nutritional interventions, and the presence of anorexia, vomiting or diarrhea at admission. Most of the dogs (84.0%) consumed less than 25% of their energy requirements and only 3.4% of the dogs met these requirements. The majority of hospitalized dogs maintained their BCS (78.2%) and BW (77%) during hospitalization. Older patients (P = 0.040), higher initial BCS (P < 0.001), and vomiting at admission (P = 0.030) were associated with a decrease of BCS status during hospitalization. BCS was also decreased in patients with low energy intake, particularly in patients with hospitalization length longer than 3 days (P < 0.001). Both longer hospitalization length (P < 0.001) and vomiting at admission (P = 0.004) were also associated with a decrease in BW. Dogs that consumed their theoretical energy requirements (P < 0.001; Odds Ratio (OR) 0.95, 95% CI: 0.92 to 0.98), and had a higher initial BCS (P < 0.001; OR 0.39, 95% CI: 0.22 to 0.63) had a lower odds of dying. Anorexia at admission (P < 0.001; OR 5.67, 95% CI: 2.23 to 15.47) was associated with a higher risk of death. The results from this study support the finding that undernutrition is relatively common during hospitalization, with age, hospitalization length, decreased energy intake, and vomiting at admission as risk factors for undernutrition. Furthermore, an association was found between inadequate energy intake and death.